2019
DOI: 10.1007/s13201-019-1053-2
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology for the optimization of acid dye adsorption onto activated carbon prepared from wild date stones

Abstract: In the present study, wild date stones (WDS) were used as a novel and sustainable precursor for high-quality activated carbon preparation to be applied for the removal of Acid Blue 25 dye (AB25) from synthetic water. The carbonization temperature of the raw material was selected at 850 °C on the basis of thermo-gravimetric analysis. The adsorbents were characterized by the BET method, Fourier transform infrared spectroscopy, and scanning electron microscopy. The results indicated that the activated carbon pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The maximum calculated adsorption efficiency was 93.2%, at 197 minutes contact time and just under 19 mg/L initial dye concentration. The interaction model results indicate that adsorption efficiency was higher with longer contact time because enough time is available for interaction between dye molecules and the adsorbent surface (Brahmi et al 2019). As can be seen, raising the adsorbent dose from 0.5 to 3 g/L increased dye removal efficiency, while the increase in initial dye concentration reduced efficiency.…”
Section: Effect Of Contact Time Vs Initial Concentrationmentioning
confidence: 89%
See 1 more Smart Citation
“…The maximum calculated adsorption efficiency was 93.2%, at 197 minutes contact time and just under 19 mg/L initial dye concentration. The interaction model results indicate that adsorption efficiency was higher with longer contact time because enough time is available for interaction between dye molecules and the adsorbent surface (Brahmi et al 2019). As can be seen, raising the adsorbent dose from 0.5 to 3 g/L increased dye removal efficiency, while the increase in initial dye concentration reduced efficiency.…”
Section: Effect Of Contact Time Vs Initial Concentrationmentioning
confidence: 89%
“…The adsorbent dose increase enhanced the availability of free active sites on the adsorbent surface (Saha et al 2012;Davarnejad et al 2020). This may occur because of the reduced ratio of active sites to dye molecules, so that there was insufficient vacant space on the adsorbent surface (Brahmi et al 2019).…”
Section: Effect Of Contact Time Vs Initial Concentrationmentioning
confidence: 99%
“…Intraparticle diffusion is the only controlling step of the process if the graph of qt versus t 1/2 passes through the origin, that is, C equals 0. If this does not occur, the mechanism is accompanied by other steps [18,39,51]. From Figure 6(D) it can be observed that the RO-16 adsorption process occurs in two consecutive steps: the first corresponds to the rapid adsorption on the external surface, that is, the dye molecules are transferred to the easily accessible active sites of the adsorbent and the second denotes the intraparticle diffusion where the adsorption stage is gradual and slow [18,37,52,53].…”
Section: 𝑙𝑛 (𝑞 𝑒 − 𝑞mentioning
confidence: 99%
“…This technique wastes time, requires a lot of experiments and uses large amounts of chemicals. These disadvantages can be overcome by optimizing the variables simultaneously using a statistical experimental design, such as the Box-Behnken design (BBD) in response surface methodology (RSM) [15,16] .…”
Section: Introductionmentioning
confidence: 99%